Territórios enoturísticos: Bento Gonçalves e a influência do terroir na criação do ecossistema criativo de pequenas cidades - Vieira, Renata Guzzatti (Universidade do Vale do Rio dos Sinos, 2020)
The present research seeks to contribute to the elaboration of strategies and guidelines that consolidate the process of territorial development of small cities that have in the terroir their main economic activity and in it the recognition as identity. For that, it is based on the concepts of Creative Cities and on the investigation of the forming elements of the Vale dos Vinhedos of Bento Gonçalves - RS to carry out the analysis as to their formation, strengths and weaknesses. After analysis, the possibilities of applying the resulting creative ecosystem in small towns are sought, seeking territorial and creative development, with the city of Urussanga - SC as the object of experiment because it has a potential wine cluster in formation. The method established was that of an instrumental case study, where through documentary data, interviews with different sectors and gathering information carried out on the object of study, it was possible to establish a comparison with the concepts covered. The data obtained were organized into 8 development actors who structure the formation of the creative cluster and the creative ecosystem resulting in the creation of application guidelines in other small cities with the terroir as an element of identity. Therefore, understanding that cities are in constant transformation, the principles of creative cities must be planned together with specific strategies and recommendations. As a result, the necessary strategy to develop the creative cluster is presented through the recognition of the terroir for the subsequent construction of the ecosystem in order to guarantee the protection of the local identity and the guarantee of territorial growth with the protected and valued identity.
Keywords: Cidades criativas; Desenvolvimento territorial; Identidade territorial; Cluster criativo; Enoturismo; Creative cities; Territoral development; Territorial identity; Creative cluster; Enoturism; ACCNPQ::Ciências Sociais Aplicadas::Arquitetura e Urbanismo